Torsion of an inguinal canal testis - Ibrahim Traoré; Rose Nandiolo Koné; Martial Olivier Moulot; Grah Franck Lohourou; Adoubs Célestin Benié; Ahua Jean Bertrand Kpangni; Constance Ursula Bony (Elsevier, 2021)
The clinical diagnosis of a torsion of an ectopic testicle is difficult. Lack of knowledge on this pathology is often a cause of late diagnosis and can have serious consequences. This diagnosis should be made in front of any acute pelvic or inguinal pain in children with an ectopic testicle, regardless of age. We report a case of late presentation of a 6 month-old infant with torsion of an ectopic testicle leading to testicular necrosis.